Kerusakan Ekosistem Laut di Perbatasan Internasional : Tantangan Politik Luar Negeri - Alfi Husni; Suherry Suherry; Safrika Nur Fadilla; Ridho Aufa Riyadi; Ferdy Dwirizki (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2024)
Marine ecosystem degradation in international border regions has evolved into a multidimensional issue that encompasses ecological, geopolitical, and diplomatic aspects. This study aims to examine how marine environmental degradation affects the foreign policy of maritime countries, particularly Indonesia, and to explore the potential of ecological diplomacy as a strategic approach. Employing a qualitative method through literature review, this research reveals that ecosystem damage in strategic areas such as the North Natuna Sea and the South China Sea not only threatens environmental sustainability but also weakens Indonesia's diplomatic standing due to fragmented maritime governance and weak environmental diplomacy. By integrating ecological considerations into foreign policy, ecological diplomacy can serve as a vital instrument for establishing inclusive and sustainable ocean governance. The study recommends strengthening inter-agency maritime coordination, modernizing marine surveillance, and expanding international cooperation based on shared ecological interests.